2020
DOI: 10.1186/s12879-020-05168-3
|View full text |Cite
|
Sign up to set email alerts
|

HIV patients retention and attrition in care and their determinants in Ethiopia: a systematic review and meta-analysis

Abstract: Background: There is paucity of evidence on the magnitude of HIV patients' retention and attrition in Ethiopia. Hence, the aim of this study was to determine the pooled magnitude of HIV patient clinical retention and attrition and to identify factors associated with retention and attrition in Ethiopia. Methods: Systematic review and meta-analysis were done among studies conducted in Ethiopia using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline. Both published and unpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 81 publications
3
24
3
Order By: Relevance
“…For the past 34 years, TASO, using its experienced and dedicated health workers, counsellors and peer educators has been closely monitoring, and providing intensive counselling and continuous education to PLHIV under TASO care, a unique support different from elsewhere. This could explain the higher retention reported in this paper compared to other studies conducted in Ethiopia [ 22 ], Mozambique [ 23 ], and Cameroon [ 24 ]. However, the retention rates reported in our study are lower than those reported in the SEARCH study conducted in Kenya and Uganda [ 20 ] and this could be attributed to the large number of patients enrolled in HIV care each month visa-vie the available resources.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…For the past 34 years, TASO, using its experienced and dedicated health workers, counsellors and peer educators has been closely monitoring, and providing intensive counselling and continuous education to PLHIV under TASO care, a unique support different from elsewhere. This could explain the higher retention reported in this paper compared to other studies conducted in Ethiopia [ 22 ], Mozambique [ 23 ], and Cameroon [ 24 ]. However, the retention rates reported in our study are lower than those reported in the SEARCH study conducted in Kenya and Uganda [ 20 ] and this could be attributed to the large number of patients enrolled in HIV care each month visa-vie the available resources.…”
Section: Discussioncontrasting
confidence: 62%
“…Overall, our study shows higher rates of retention for PLHIV compared to other studies conducted elsewhere [ 22 – 24 ]. For the past 34 years, TASO, using its experienced and dedicated health workers, counsellors and peer educators has been closely monitoring, and providing intensive counselling and continuous education to PLHIV under TASO care, a unique support different from elsewhere.…”
Section: Discussioncontrasting
confidence: 53%
“…These numbers are similar to those of the monoinfected group in this study but significantly lower than those found in the coinfected group. A systematic review in Ethiopia showed an overall attrition of 21% in HIV-positive people enrolled for ART care, which is also comparable with the monoinfected cumulative attrition in this study even after excluding those transferred out from our analysis; the other study considered transferred-out patients to be retained on ART [ 24 ]. Therefore, direct comparison with this study may not be reasonable.…”
Section: Discussionsupporting
confidence: 79%
“…Major risk factors to LTFU from ART programmes include several sociodemographic (male sex, older age, being single, unemployment, lower educational status), clinical (advanced WHO stage, low weight, worse functional status), patient behaviour (poor adherence, nondisclosure), treatment related and system level factors [ 7 ]. A systemic review of a pooled magnitude of HIV patient clinical retention and attrition in Ethiopia found out that major determinants of attrition were being unmarried patient, non-disclosed HIV status, poor drug adherence, poor functional status, being underweight and advanced clinical stage [ 8 ]. Knowledge of risk factors should be used to better develop retention interventions in HIV programmes.…”
Section: Introductionmentioning
confidence: 99%